PENGARUH BUKU AJAR BERMUATAN KECERDASAN KOMPREHENSIF DALAM MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP KOMPETENSI FISIKA PESERTA DIDIK KELAS X SMAN 9 PADANG - Junaidy Syam; Asrizal Asrizal; Zulhendri Kamus (Universitas Negeri Padang, 2017)
Development the holistic comptences of learners is important in 2013 curriculum for all subjects. In another side development of holistic comptence of learners aren’t implemented in physics learning in high school yet. As solution of this problem is to implement learning textbook by integrating comprehensive intelligence in problem based learning model. The objective of this research is to investigate the difference competence of learner and to investigate the effect of learning textbook by integrating comprehensive intelligence. The type of this research is quasy experiment with randomized control group only design. As population of this research is all learners grade X MIA in SMAN 9 Padang that leasted in 2016/2017 years. Sampling technique in this research is purposive sampling. There are three instruments in this research, those are test sheet, observation sheet, and performance sheet. Data are analysis by descriptive statistic compare mean test, linear regresion, and corelation analysis. There are two of research results. First result is the implementation of learning textbook by integrating comprehensive intelligence in problem based learning model has given significant difference competence of learners including knowledge, spiritual, social and emotional, and skills competence. Second resul is the implementation of learning textbook by integrating comprehensive intelligence in problem based learning model has given significant effect to improve knowledge, spiritual, emotional and social, and skills competences of learner respectly 27,04%, 33,67%, 31,47%, and 17,64 %